2006
DOI: 10.1063/1.2260825
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress in Si nanocrystals embedded in a SiO2 matrix

Abstract: Multiple quantum wells consisting of alternating Si and SiO2 layers were studied by means of Raman scattering. The structures were fabricated by the remote plasma enhanced chemical vapor deposition of amorphous Si and SiO2 layers on quartz substrate. The structures were subjected to a rapid thermal annealing procedure for Si crystallization. The obtained results suggest that the Si layers consist of nanocrystals embedded in an amorphous Si phase. It was found that the silicon nanocrystals inside 2nm thin layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 16 publications
7
71
0
Order By: Relevance
“…66 In 2006, Arguirov et al reported the formation of BC8 Si NPs within amorphous Si in a-Si/SiO 2 multilayer stacks. 69 In addition, Smith et al 8 showed that R8 and BC8 NPs are formed when "black silicon" is produced by irradiating highly doped Si surfaces with femtosecond laser pulses. The authors argued that pressure waves generated by the fspulses first amorphized regions of the sample and then induced the nucleation of R8 and BC8 NPs within these regions.…”
Section: B Embedded Si Nanoparticlesmentioning
confidence: 99%
“…66 In 2006, Arguirov et al reported the formation of BC8 Si NPs within amorphous Si in a-Si/SiO 2 multilayer stacks. 69 In addition, Smith et al 8 showed that R8 and BC8 NPs are formed when "black silicon" is produced by irradiating highly doped Si surfaces with femtosecond laser pulses. The authors argued that pressure waves generated by the fspulses first amorphized regions of the sample and then induced the nucleation of R8 and BC8 NPs within these regions.…”
Section: B Embedded Si Nanoparticlesmentioning
confidence: 99%
“…Silicon nanocrystals are frequently characterized by means of Raman spectroscopy that provides very detailed information on their crystal structure [8][9][10][11]. For bulk Si, triply degenerate (T 2g ) first-order optical phonon at the Brillouin-zone centre is observed at 521 cm -1 .…”
Section: Introductionmentioning
confidence: 99%
“…While complete transformation of DC-Si to β-Sn-Si (and thereby BC8) requires pressures in excess of 10 GPa, recent studies indicate that chemical pathways involving sodium can reduce the formation pressure to as low as 7 GPa without the formation of β-Sn-Si [14]. In addition, an ambient-pressure colloidal synthesis route for BC8-Si nanoparticles was recently reported [15], which may serve useful for solar energy conversion applications with multiple exciton generation [16,17].…”
mentioning
confidence: 99%